OUTCOME OF PERCUTANEOUS NEPHROLITHOTOMY IN PRE-SCHOOL AND SCHOOL-AGE CHILDREN-SINGLE CENTER EXPERIENCE - Iqbal, Nadeem; Hasan, Aisha; Sami Siddiqui, Fasih; ftikhar, Faisal; Maryam Ilyas, Syeda; Hussain, Ijaz; Khan, Faheemullah; Akhter, Saeed (Journal of Ayub Medical College Abbottabad, 2019)
Background: Efficacy of percutaneous nephrolithotomy in adults has been studied well in past. However, such studies are sparse within paediatric age group. As this procedure is being adopted in smaller and older children alike, we wanted to determine its safety and efficacy in two different age groups of children (preschool age and school age). Methods: The records of 59 children undergoing PCNL at our department from December 2009 to May 2017 were reviewed retrospectively. Patients were placed into 2 age groups including children ‰¤7 years old (group 1) and those ‰¥7 years (group 2). Twenty-seven patients were put in preschool group with mean age of 4.8±2.1 years while 32 patients in school age group having mean age of 11.8±4.6 years. Results: Stone size was calculated showing mean 309±55 mm2 in preschool and 324±63 mm2 in school age group respectively (p=0.1). The mean operative time was 150.1±38.7 minutes and 166.3±39.6 minutes in the preschool and school age children respectively (p=0.1). The mean length of hospital stay was 3.1±1.4 days and 2.9±1.3 days in preschool and school going children (p=0.5). The stone clearance with PCNL was seen in 96.3% (pre-school group) and 93.75% (school age group) as monotherapy (p=0.1), which increased to 100% after combining it with extracorporeal shock wave lithotripsy. Conclusion: PCNL is equally effective in both pre-school and school age groups in terms of stone free rates. Complication rates were not different between the two groups. Keywords: Renal Stones; Paediatric Nephrolithiasis; Per-cutaneous nephrolithotomy; Stone clearance